BeNTO: Beam Network Topology Optimization. (March 2023) - Morris, Nigel J.W.; Jayaraman, Pradeep Kumar; Butscher, Adrian
Abstract: We present an optimization framework that allows designers and engineers to develop conceptual designs for structures that can be manufactured using a network of connected beams. We leverage level set-based topology optimization along with a graph representation extracted from the skeleton of the level set. This graph is used to create an idealized beam network of the structure and the level set and the beam networks co-evolve during the course of the optimization. We propose a constraint that moves the level set geometry closer to this beam network and ultimately drives the two representations to converge. The graph representation also enables us to enforce manufacturability in the beam network, including minimum and maximum cross-section size, angle snapping and cross-section continuity. By applying the beam constraint during topology optimization we are able to generate designs that satisfy the structural requirements and can also be fabricated as beam networks. We present several example sets that illustrate the beam networks that can be generated, how they compare to results without the beam constraint as well as the impact of the manufacturability methods. Highlights: Framework for designing beam networks using level set topology optimization. Co-evolve the beam network with the level set and drive both toward convergence. Manufacturability controls can easily be defined on the beam network.